Plasmodium falciparum and intestinal parasitic co-infections in HIV-infected patients in Benin City, Edo State, Nigeria - Akinbo, Frederick Olusegun; Okaka, Christopher Ehis; Omoregie, Richard (The Journal of Infection in Developing Countries, 2011)
Introduction: Human co-infection with Plasmodium falciparum and helminthes is ubiquitous throughout Africa. This study aimed to determine the co-infections of Plasmodium falciparum infection in HIV and intestinal parasitic infections, and their immunological distribution, in Benin City, Nigeria. Methodology: A total of 2,000 stool specimens from HIV-positive patients and 500 controls (HIV-negative individuals) were examined for ova, cysts, or parasites using standard procedures. In addition, patients' blood samples were analyzed for CD4 counts by flow cytometry and examined for Plasmodium falciparum by microscopy. Results: The prevalence of single parasitic infection among HIV patients was 18.1% in males and 16.9% among females with no significant difference (p = 0.536) while gender was a risk factor in multiple parasitic infections (male versus female: 4.2% and 1.8% OR = 2.384; 95% CI = 1.371, 4.147) (p = 0.0025). Increasing age was not associated with increased risk of both single and multiple parasitic infections (p = 0.083; p = 0.248). CD4 + T cell count less than 200 cells/µl was a risk factor for acquiring single and multiple parasitic infections among HIV patients (OR = 5.565; 95% CI = 4.136, 7.486; p = 0.0001; OR = 4.283; 95% CI = 2.424, 7.566; p = 0.0001). The most common co-infection observed was between Plasmodium falciparum and Ascaris lumbricoides 43% (10) among HIV patients. Conclusion: This study provides evidence of co-infections between Plasmodium falciparum and intestinal parasites. Diagnosis of parasitic infections among HIV patients is advocated as this will enhance better management of HIV-infected patients.